Plasma neutrophil gelatinase-associated lipocalin best diagnosed acute kidney injury in patients with systemic inflammatory response syndrome and sepsis - Md Ralib, Azrina; Abdullah, Nor Zamzila; Mohamed, Rozilah @ Abdul Hadi; Mat Nor, Mohd Basri (2015)
Introduction: Sepsis is the leading cause of ICU admission. About 60% of patients with severe sepsis had acute kidney injury (AKI). To date, plasma Neutrophil-Gelatinase Associated Lipocalin (NGAL) is the most promising biomarker for AKI, however it is also increased with inflammation and infection.